Regulation of the hypoxia-dependent plasminogen activator inhibitor 1 expression by MAP kinases - Kietzmann, Thomas; Jungermann, Kurt; Görlach, Agnes (Thrombosis and Haemostasis, 2003)
Mitogen-activated protein kinases (MAPKs) and protein kinase B (PKB) mediate growth and stress signals and have been implicated in the hypoxic response. Under hypoxic conditions, the expression of plasminogen activator inhibitor-1 (PAI-1) is mainly controlled by the hypoxia-inducible factor HIF-1. However, the role of MAPKs and PKB in HIF-1-mediated PAI-1 regulation is not clear.Treatment with the p38 inhibitor SB203580 and the PI3K inhibitor LY294002, but not with the MEK1 inhibitor PD98059, abrogated hypoxia-dependent PAI-1 induction in HepG2 cells. Consistently, overexpression of PKB or of the p38 upstream kinases MKK6 and MKK3 and of JNK, but not of ERK, enhanced PAI-1 mRNA levels. In MKK3-,MKK6- and PKB-expressing cells luciferase (Luc) activities from a hypoxia-inducible PAI-1-Luc construct or from a HIF-dependent Luc construct and, concomitantly, HIF-1α protein levels were enhanced. These findings indicate that p38- and PKB-dependent signalling pathways contribute to enhanced PAI-1 levels in the hypoxic response.Theme paper: Part of this paper was originally presented at the joint meetings of the 16th International Congress of the International Society of Fibrinolysis and Proteolysis (ISFP) and the 17th International Fibrinogen Workshop of the International Fibrinogen Research Society (IFRS) held in Munich, Germany, September, 2002.
Keywords: PAI-1; MAP kinases; hypoxia; thrombosis